Signal-based deployment planning for robot teams in tunnel-like fading environments. (October 2013) - Rizzo, C.; Tardioli, D.; Sicignano, D.; Riazuelo, L.; Villarroel, J. L.; Montano, L.
Deploying a multi-robot team in confined environments poses multiple challenges that involve task and motion planning, localization and mapping, safe navigation, coordination of robots and also communications among all of them. In recent years, increasing attention has been paid to these challenges by the robotics community, but many problems remain unresolved. In this paper we address a technique for planning the deployment of a robot team in so-called fading environments, such as tunnels or galleries, where signal propagation presents specific characteristics. In order to maintain constant connectivity and high signal quality in the communication network formed by the robots and the base station, the robot deployment is driven by real-time signal measurements. First, an analysis of the signal propagation to obtain the general characteristic parameters of the signals in this kind of environment is carried out. Second, a technique which uses these parameters to drive the deployment is developed. A general strategy for this kind of environment in which the signals exhibit similar behavior is implemented. A complete system involving all of the above-mentioned robotics tasks has been developed. Finally, the system has been evaluated by means of simulation and in a real scenario.